Microbiological Quality and Safety of Raw Sheep Milks from Native Epirus Breeds: Selective Effects of Thermization on the Microbiota Surviving in Resultant Thermized Milks Intended for Traditional Greek Hard Cheese Production - John Samelis; Loulouda Bosnea; Athanasia Kakouri (Applied Microbiology)
Thermization is a sub-pasteurization heat treatment widely applied in traditional Greek hard cheese technologies. In this study, five bulk milk batches from two native Epirus sheep breeds were analyzed microbiologically before (raw milk; RM) and after thermization at 65 °C for 30 s (TM) followed by characterization of 125 presumptive LAB isolates from each of the counterpart RM and TM samples. Psychrotrophic Pseudomonas-like spoilage bacteria and mesophilic LAB, primarily of the genera Leuconostoc (48.4%) and Lactococcus/Streptococcus (32.8%), co-dominated in RM at mean levels 5.7–6.3 log CFU/mL, whereas thermophilic LAB, Enterococcus, Staphylococcus, coliforms, and yeasts were subdominant at mean levels 4.1 to 5.2 log CFU/mL. Coagulase-positive staphylococci were abundant (3–4 log CFU/mL) in all RM batches. Listeria monocytogenes was found in one batch. Both pathogens were diminished by thermization, which reduced all non-LAB contaminants below 100 CFU/mL. Enterococci (68.6%) were highly selected in all TM batches, followed by thermophilic streptococci (8.6%). Only 7.4% of the total RM microbiota survived in the resultant five TM batches. Leuconostoc showed the lowest (1.3%) survival. Thus, thermization improved the quality and safety of raw sheep milk, but reduced mesophilic LAB by ca. 2 log units in favor of enterococci in TM.